Cell interactions in the immune response in vitro. V. Specific collaboration via complexes of antigen and thymus-derived cell immunoglobulin. - Feldmann, M (1972)
The mechanism of interaction of T and B lymphocytes was investigated in an in vitro hapten carrier system using culture chambers with two compartments separated by a cell impermeable nucleopore membrane. Because specific cell interaction occurred efficiently across this membrane, contact of T and B lymphocytes was not essential for cooperation which must have been mediated by a subcellular component or "factor." By using different lymphoid cell populations in the lower culture chamber and activated thymus cells in the upper chamber (with antigen present in both), it was found that the antigen-specific mediator acted indirectly on B cells, through the agency of macrophages. Macrophages which had been cultured in the presence of activated T cells and antigen acquired the capacity to specifically induce antibody responses in B cell-containing lymphoid populations. Trypsinization of these macrophages inhibited their capacity to induce immune responses, indicating that the mediator of cell cooperation is membrane bound. By using antisera to both the haptenic and carrier determinants of the antigen as blocking reagents, it was demonstrated that the whole antigen molecule was present on the surface of macrophages which had been exposed to activated T cells and antigen. Because specifically activated T cells were essential a component of the antigen-specific mediator must be derived from these cells. By using anti-immunoglobulin sera as inhibitors of the binding of the mediator to macrophages, the T cell component was indeed found to contain both kappa- and micro-chains and was thus presumably a T cell-derived immunoglobulin. It was proposed that cell cooperation is mediated by complexes of T cell IgM and antigen, bound to the surface of macrophage-like cells, forming a lattice of appropriately spaced antigenic determinants. B cells become immunized by interacting with this surface. With this mechanism of cell cooperation, the actual pattern of antigen-B cell receptor interactions in immunization would be the same with both thymus-dependent and independent antigens. An essential feature of the proposed mechanism of cell cooperation is that macrophage-B cell interaction must occur at an early stage of the antibody response, a concept which is supported by many lines of evidence. Furthermore this mechanism of cell interaction can be elaborated to explain certain phenomena such as the highly immunogenic macrophage-bound antigen, antigenic competition, the distinction between immunity and tolerance in B lymphocytes, and the possible mediation of tolerance by T lymphocytes.